HPV16 E6 oncoprotein promotes microhomology-mediated viral integration by increasing PolΘ protein expression - Guangli Zhu; Shuhei Asada; Jithma P. Abeykoon; Lifang Sun; Sirisha Mukkavalli; Alan D. D’Andrea (Proceedings of the National Academy of Sciences, 2026)
Integration of the high-risk human papillomavirus 16 (HPV16) genome into the host chromosome, frequently driven by microhomology-mediated end joining (MMEJ), is a critical step in the carcinogenesis of HPV-associated tumors. However, the mechanisms by which viral oncoproteins manipulate the error-prone MMEJ pathway remain poorly defined. Here, we demonstrate that the HPV16 E6 oncoprotein upregulates MMEJ to facilitate viral genome integration. This heightened MMEJ activity is driven by a marked increase in the protein levels of DNA polymerase theta (PolΘ), a central enzyme of the MMEJ pathway. Mechanistically, we show that the elevation of PolΘ levels in response to HPV16 E6 expression is dependent on the host E3 ubiquitin ligase UBE3A/E6AP but is independent of p53 degradation. E6 redirects UBE3A to enhance the ubiquitination and degradation of RAD23A, a shuttle protein required for delivering polyubiquitinated PolΘ to the proteasome. Consequently, the loss of functional RAD23A phenocopies the effect of HPV16 E6, leading to PolΘ protein stabilization and increased MMEJ activity. By elucidating the E6-UBE3A-RAD23A-PolΘ axis, our findings reveal a mechanism through which HPV manipulates the host DNA repair machinery to promote its integration and oncogenic potential.